Tourism in marine protected areas experiences from Nha Trang Bay, Viet Nam - Thuy, Pham Thi Thanh (Los Baños, Laguna, Philippines WorldFish (ICLARM) - Economy and Environment Program for Southeast Asia (EEPSEA), 2016)
This study examines how tourism affects biodiversity conservation and the well-being of local communities in Nha Trang Bay marine protected area in Viet Nam. Data was collected from 140 households, various industries, and government bodies. Secondary data were also used. The findings show that tourism is a mixed blessing. The tourism industry has had a negative impact on marine biodiversity, whereas the effects on communities’ well-being are both positive and negative. Hence, the paper questions the notion of “ecotourism” and discusses what can be done to make tourism more sustainable.
"October, 2016"
Includes bibliographical references (pages 22-26)
Keywords: Marine parks and reserves -- Vietnam -- Management; Protected areas -- Vietnam -- Management; Tourism -- Vietnam